2019
DOI: 10.1007/s11192-019-03234-5
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis in motorcycle accident research: a global overview

Abstract: 770 million motorcycles are estimated on the roads. Motorcyclists represent more than 380,000 annual deaths worldwide. 28% of the global fatalities in the roads in 2016. With the increase of the accident rate, studies have been developed within the scientific literature. Bibliometric analysis is applied in the field of motorcycle safety in order to identify relevant publications on risk factors of road crashes and their implications. The information in this research was extracted from Web of Science and Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 61 publications
0
32
0
6
Order By: Relevance
“…The academic impact and relative influence of research on industrial clusters and global value chains is measured through the use of evaluative techniques. Accordingly, productivity is assessed based on the historical evolution of publications, the distribution of articles by journal or book and also by individual author ( Ospina-Mateus et al, 2019 ). In addition, the most cited documents allows us to evaluate the impact or relative influence of the topic ( Hall, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The academic impact and relative influence of research on industrial clusters and global value chains is measured through the use of evaluative techniques. Accordingly, productivity is assessed based on the historical evolution of publications, the distribution of articles by journal or book and also by individual author ( Ospina-Mateus et al, 2019 ). In addition, the most cited documents allows us to evaluate the impact or relative influence of the topic ( Hall, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The bibliometric study done by Shanker et al ( 2020 ) analysed the studies of neurosurgeon’s academic works in the New York metropolitan area. Another bibliometric study was by Iwami et al ( 2019 ) who examined fields that co-evolved with information technology while (Ospina-Mateus et al 2019 ) analysed the study of motorcycle accidents. A study by Baker et al ( 2019 ) in the field of financial economics used bibliometric analysis to present the productivity and impact of RFE (review of financial economics).…”
Section: Methodsmentioning
confidence: 99%
“…Several pieces of research [30][31][32] have concluded that the crashes and fatalities suffered by male motorcyclists are higher and more severe than those of women, with the young drivers prone to have more accidents. Overall, research on causality and the severity of traffic accidents holds a dominant position in research trends about motorcycle accidents [33].…”
Section: Introductionmentioning
confidence: 99%